Synthesis of long-chain fatty acid starch esters in aqueous medium and its characterization. (October 2019) - Zhang, Kairui; Cheng, Fei; Zhang, Kang; Hu, Jianbo; Xu, Changxue; Lin, Yi; Zhou, Mi; Zhu, Puxin
Graphical abstract: Highlights: Esterified starch was synthesized by water media method. Stearic or lauric acid was used to esterify with starch in urea/NaOH solutions. The substitution degree of starch esters are higher than the reported values. The starch esters, with lower crystallinity, had better performance than starch. The starch esters had higher glass transition temperature within the limited DS. Abstract: Long-chain fatty acid starch esters are prepared by esterification of stearic acid or lauric acid with corn starch in urea/NaOH aqueous solutions. Effect of esterify condition on the degree of substitution (DS) and the structure and performance of the products are studied. The synthesized starch stearate and starch laurate are obtained a DS of 0.065 and 0.074, respectively, higher than the reported values by the water medium method. Esterification of starch is proved by Fourier transformed infrared and 1 H nuclear magnetic resonance. The structure and thermal properties of starch esters are confirmed by X-ray diffraction, Scanning Electron Microscope, Thermogravimetry and Differential Scanning Calorimetry. The results show that the starch esters, with lower crystallinity than starch, has better thermostability, emulsibility, transparency, freeze-thaw stability and moisture absorption than native starch, but higher glass transition temperature ( T g ) within the limited DS.